Jejak Peran Orang Nusalaut Dalam Pelayaran Hongi - Wattimury, Samuel Michael; Batkunde, Arnold; Pattiasina, Johan (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2021)
The existence of Maluku as a source of spices, including cloves, nutmeg, and mace, is like a magnet that attracts various nations to come to seek and control them. As part of the Lease archipelago, Nusalaut plays an important role in the policy of the “Hongietochten” expedition or Hongi voyage. The research aims to find out the traces of the role of the Nusalaut people in the Hongi voyage? by using the historical method through four stages: Heuristics, Verification, Interpretation and Historiography. Based on this research method, it was found that the people of Nusalaut were charged with great responsibility in the process of making the Beverwijk Fort and the Old Church of Ebenhaezer in Sila; the people of Nusalaut also carried out a departure from the “Negeri Lama” in the mountainous area to descend and inhabit the coastal region, In addition, it is noted that the Christianization process in Nusalaut is growing rapidly, there is also the development of clove cultivation technology, as well as the introduction of new technology in the manufacture of buildings from sea stones that are burned into lime.